Exploring PTSD in Adolescents: A Study of Senior High School Students in Bandung - Popy Mayasari Afendy; Muqaffi; Nadiya Kurniati; Ahman; Mutiara Aqilla Tasya (Universitas Negeri Semarang, 2025)
Post-traumatic stress disorder (PTSD) is a psychological disorder that occurs in response to traumatic events. This condition is prone to occur in adolescents due to their ongoing psychological development. This study aims to reveal the profile of post-traumatic stress disorder in adolescents in Bandung City. The methods use a quantitative survey design. The research subjects involved in this study were active students attending school in Bandung City. This study used a PTSD questionnaire consisting of seven items and developed based on the PTSD construct to reveal the profile of PTSD in adolescents. The questionnaire has been tested for reliability with a Cronbach's Alpha value of 0.794. The results showed that the most significant factor of PTSD affecting students was the experience of being “haunted by traumatic events.” Meanwhile, the aspect of ‘low expectations for the future’ had a smaller impact. These findings indicate that, although students are greatly affected by PTSD symptoms such as intrusive memories and emotional distress, most still maintain a positive outlook on their future. This study expected to contribute for understanding of PTSD manifestations in adolescents and has significant potential as a foundation for strengthening adolescents' perspectives on their future.